SCENARIO PLANNING PEMBANGUNAN SUMBER DAYA KELAUTAN DI KABUPATEN NATUNA* - Hastuti Hastuti (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2008)
Scenario Planning of Marine Resource Development in Natuna RegencyThis study aims at finding out the description about the implementation of marine resource development in Natuna Regency as the source of analysis for formulating the draft of long-term planning scenario of marine resource in Natuna Regency. The approaches of this study are system thinking and system dynamics. Systems thinking approach is for designing a model based on the study on concept, theory, reality and innovation. The model is then simulated through system dynamics to examine the validity and to intervene thepolicy upon the established model. This simulation on model results in scenario planning of marine resource development in Natuna Regency that is designed based on four scenario classifications (based on Ringland matrix). These scenarios are then arranged in three groups of study covering; 1) scenario on marine resource potential and fleet development towards the number of caught fish, 2) scenario on fleet development and fish marketing towards the income of caught fishery, and 3) scenario on fish basket development towards the production of cultivated fish and towards fishery income. The above scenarios are then proceeded by analysis of policy intervention, and by formulation ofstrategy to improve the future development of marine resource intended to develop the social welfare.